2022
DOI: 10.3389/fnagi.2022.1016293
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular communication analysis of the human retinal pigment epithelial and choroidal cells predicts pathways associated with aging, cellular senescence and age-related macular degeneration

Abstract: The retinal pigment epithelium (RPE) and the choroid are ocular tissues with fundamental roles in supporting neuroretinal function. The pathogenesis of age-related macular degeneration (AMD), a leading cause of irreversible blindness for which aging is the highest risk factor is closely linked with progressive impairment of various functions of these tissues. Cellular senescence, marked by cell cycle arrest and secretion of proinflammatory factors, is known to be associated with aging and has been proposed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 90 publications
2
2
0
Order By: Relevance
“…In order to further elucidate the molecular mechanism of miR-100 in AMD, we identi ed BMPR2, the downstream target of miR-100, using StarBase and TargetScan. Dhirachaikulpanich et al revealed that decreased expression of BMPR2 receptor in human choroidal endothelial cells during aging [27]. In this study, depletion of BMPR2 accelerates senescence, oxidative stress, and DNA damage in H 2 O 2treated ARPE-19 cells.…”
Section: Discussionsupporting
confidence: 53%
“…In order to further elucidate the molecular mechanism of miR-100 in AMD, we identi ed BMPR2, the downstream target of miR-100, using StarBase and TargetScan. Dhirachaikulpanich et al revealed that decreased expression of BMPR2 receptor in human choroidal endothelial cells during aging [27]. In this study, depletion of BMPR2 accelerates senescence, oxidative stress, and DNA damage in H 2 O 2treated ARPE-19 cells.…”
Section: Discussionsupporting
confidence: 53%
“…Figure 2i-j show example interaction plots in the human trachea tissue. T cells and epithelial cells are among the top interaction targets of SnCs 12,29 (Figure 2k), consistent across human and mouse (correlation=0.417, Figure 2l, Supplementary Table S4). Several key pathways known as hallmarks of cellular senescence are consistently enriched across tissues (Figure 2m), including COLLAGEN, which is responsible for extracellular matrix remodeling and enlarged phenotypes of senescent cells 30-32 ; LAMININ, corresponding to the loss of laminin B1 that compromises nuclear integrity in senescent cells 1,33 ; MHC-I, which is elevated in senescent cells 34,35 ; and MIF, which is involved in senescence-associated inflammation and oxidative stress response pathways 36,37 .…”
Section: Mainsupporting
confidence: 52%
“…Senescent cells are metabolically active and can communicate with, and influence the behaviour of, neighbouring cells through paracrine signalling [ 231 ]. Senescence is also an important part of inter-cellular communication and ageing [ 232 ] via SASP [ 233 ]. As well as the secretion of pro-inflammatory molecules, senescent cells also communicate with other cells via membrane-bound intercellular bridges or ‘tunnelling nanotubes’, that facilitate direct physical connections between cells [ 234 ].…”
Section: Molecular Hallmarks Of Ageing In Alsmentioning
confidence: 99%